The diversity of soil parasitic protists shapes ecosystem stability worldwide - Bing Wang; Dima Chen; Shuaifei Wang; Liji Wu; Ying Wu; Shengen Liu; Manuel Delgado-Baquerizo (Proceedings of the National Academy of Sciences, 2026)
Soil parasitic protists influence the health of plants and soil organisms. Yet, the extent to which these interactions impact the stability of terrestrial ecosystems remains largely unquantified. Here, we utilized two independent global-scale biodiversity surveys available online to investigate the relationship between the taxonomic diversity of parasitic protists and satellite-based time series of ecosystem productivity (i.e., normalized difference vegetation index). We found that soil parasitic protist diversity, particularly the diversity of Apicomplexa (common parasites of soil invertebrates), was consistently and positively correlated with ecosystem temporal stability worldwide. Our analyses suggest that Apicomplexa diversity is positively associated with temporal stability of ecosystem productivity by boosting mean productivity, likely through regulating invertebrate plant herbivory and nutrient cycling. Furthermore, the relationships between Apicomplexa diversity and ecosystem temporal stability were strongly mediated by climate, with a stronger correlation found in less productive colder or drier ecosystems. Our findings provide large-scale empirical evidence for the previously undescribed significant statistical relationship between soil parasitic protist diversity and ecosystem stability, highlighting their potential role in explaining the stability of terrestrial ecosystems globally.